Pengaruh Penyimpan Panas Pada Alat Pengering Surya Pemanasan Langsung Tipe Kabinet Terhadap Temperatur Dan Massa Bahan Pisang Yang Dikeringkan - Krisna Bayu Saputra; Azridjal Aziz (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Solar energy is one source of energy that has an unlimited amount, making it the largest source of energy reserves on earth. The utilization of the commonly used is radiation energy in a solar drying apparatus. A solar type solar dryer cabinet is a direct heating type solar dryer that utilizes natural convection to heat a cabin shaped air. The cabinet dryer consists of a solar collector and an integrated drying chamber. The research methodology used in this study is an experimental method to determine the performance of two types of solar dryer type cabinet. One of the cabinet type solar powered dryer uses sensible heat storage in the form of a split stone. Thermal energy storage or heat is a system that storage heat from surrounding. The heat energy storage system is divided into two, namely sensible calorie storage system and latent heat storage system. The average temperature of a banana on a solar power dryer with a heat storage medium is 39oc with the highest temperature on the second shelf is 52.7oc while the banana temperature on the solar power dryer without heat storage medium is 37oc and the highest temperature on the second shelf is 51.7oc. The final water content contained in the banana after drying on the dryer with the heat storage medium is 36% and in drying apparatus without a heat storage medium is 45.2% . The efficiency of the test using a solar power dryer with a heat storage medium is obtained 28.4%, while for testing using a solar power dryer without heat storage media that is equal to 26.1%.Keywords: Solar dryer, Sensible Heat storage, Split stone